Analisis Penerapan Keselamatan dan Kesehatan Kerja (K3) dengan Kejadian Kecelakaan Kerja pada Perawat di Rumah Sakit X - Albert Hasibuan; I.Gusti Ngurah.Y.Usdayana; Halisa Kurniati; Fransiscus A.C.Wakumoan (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Occupational accidents are unexpected events. Incident of occupational accident often happened to health officer especially nurse. Therefore, it is necessary efforts to foster the implementation of occupational safety and health (OHS) in order to avoid occupational accident. The aim of this research is to analyze the effect of implementation occupational health and safety (OHS) (knowledge, attitude, training, promotion and supervision) of the incidence of occupational accidents for nurses at Hospital X in 2025.The research is quantitative analytic survey research using Cross-sectional Analitics. The Population is all nurses from Outpatient room and Inpatient room at Hospital X. Its amounted to 164 people, using technique of total population. Data analysis with univariate analysis, bivariate analysis with chi square test, multivariate analysis with multiple logistic regression test. The results of the reaserch showed that effect occupational accidents are attitude p value 0,001, training p value 0,001, promotion p value 0,001 and the confounding is a knowledge variable to training variable. The conlusion of the research is to make the implementation of occupational health and safety become the most important for nurse. Recommended to the Hospital X along with occupational health and safety committee to improve the knowledge of nurses on occupational health and safety through socialization, training, and internal meeting of the periodic.